PENGARUH KEPEMIMIPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP LOYALITAS YANG BERDAMPAK PADA KINERJA KARYAWAN DI PERUSAHAAN - Amri, Ricky Fabiano (JURNAL BISNIS STRATEGI, 2016)
PT. Kimia Farma Plant Semarang Manufacturing is one of the State Owned Enterprises (SOEs) specializing in the pharmaceutical field, in which for the production activity in the region is in manufacturing cosmetics Seamarang national scale. In 2012 the performance of employees of PT. Kimia Farma Plant Semarang Manufacturing decreased from previous years. Therefore, this study was conducted to determine how to improve the performance of employees at PT. Kimia Farma Manufacturing Plant Semarang.This research was conducted by analyzing the factors that affect the performance of employees with transformational leadership variable, job satisfaction variable and loyalty variable as an intervening variable. This research by developing a theoretical model by proposing five hypotheses to be tested by using Partial Least Square (PLS) as an analytical tool. The respondents of this study were all employees of PT. Kimia Farma Manufacturing Plant Semarang totaling 80 people.The results of data processing by using PLS to the theoretical models have met the discriminant validity, value Average Variance Extracted (AVE) and the Test of Composite Realibility. The processing results can be stated that the model meets the criteria for a reliable and feasible for use. These results indicate that employee performance can be improved by job satisfaction and transformational leadership. Perception of transformational leadership are good and high job satisfaction will affect the performance of employees of PT. Kimia Farma Manufacturing Plant Semarang.